Comparative morphometric analysis of erythrocytes among several reptile species using ImageJ - Mahendra, Arindina; Santoso, Koekoeh; Suprayogi, Agik; Maheshwari, Hera; Tarigan, Ronald; Manalu, Wasmen; Ekastuti, Damiana Rita; Satyaningtijas, Aryani Sismin; Achmadi, Pudji; Isdoni; Abdullah, Nur Rahmah (Journal of Wildlife and Conservation Medicine, 2026)
Background The morphometry of erythrocytes is highly correlated to their metabolic rate and metabolic demand of the species, which causes the main difference between reptiles and mammals. Reptiles are ectotherms which has very low metabolic rate, but have variation to its metabolic demand due to the differences between its phylogenetic, habitat, and behavior. Objective The present study aimed to compare erythrocyte morphometry among several reptile species. Methods Blood smear samples that were obtained from published articles and analysed using ImageJ software. Surface area and circularity of erythrocyte and its nucleus were analyzed, and the surface area ratio between erythrocyte and nucleus was calculated. Results Sea turtle that spends most of its life in the sea has the smallest erythrocyte (84.04 ± 7.24 µm2) due to its behavior to dive and requires more rapid and effective blood gas exchange. Meanwhile, terrestrial reptiles that have passive behavior, such as Boa snakes, have the largest erythrocyte (270.59 ± 10.12 µm2), which allows a slow circulatory rate but can also carry more gas during activity. Conclusion This comparative study showed that not only the phylogenetic characteristics of a species, but also habitat and behavior that affect metabolic rate and blood gas exchange are reflected in the morphometry of erythrocytes.